2009
DOI: 10.4103/0253-7176.53310
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Perspectives on Spirituality and Mental Health

Abstract: The paper strives to elucidate the complex yet intimate relation between spirituality and mental health from contemporary perspectives. The diverse and constantly evolving views that spiritualists and mental health professionals have held toward each other over last century are discussed with special accent on the transpersonal spiritual framework within psychology. The role of spirituality in promoting mental health and alleviating mental illness is highlighted. The paper is concluded with an increasing need … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 31 publications
0
15
0
1
Order By: Relevance
“…A lot of psychotherapists believed that psychotherapy by itself is a spiritual activity. Spirituality is being increasingly recognized in the mental health field as having a huge potential for improving the mental, physical and ethical problems of individuals and society (Sharma et al, 2009). Cognitive-behavioral therapy is a useful management of mental and psychological disorders.…”
Section: The Role Of Spirituality On the Development Of Virtues And Gmentioning
confidence: 99%
See 2 more Smart Citations
“…A lot of psychotherapists believed that psychotherapy by itself is a spiritual activity. Spirituality is being increasingly recognized in the mental health field as having a huge potential for improving the mental, physical and ethical problems of individuals and society (Sharma et al, 2009). Cognitive-behavioral therapy is a useful management of mental and psychological disorders.…”
Section: The Role Of Spirituality On the Development Of Virtues And Gmentioning
confidence: 99%
“…Yogic treatments can effectively cure and prevent a lot of diseases ranging from hypertension, asthma, heart disease, cancer, multiple sclerosis, and diabetes. Spirituality helps depressive patients to regain the meaning or a purpose in their life, which they had lost due to their illness (Sharma et al, 2009). A study found that for every 10-fold increase in a person's intrinsic religiosity, there was a 70% increase in recovery from depressive symptoms (Koenig et al, 1998).…”
Section: The Role Of Spirituality On the Development Of Virtues And Gmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between spirituality and mental health has been documented (Sharma et al ., 2009[43]). By virtue of training, the psychiatrist can understand spiritual and existential issues of both patients and their caregivers and address spiritual pain and suffering in EOLC.…”
Section: Role Of Psychiatry In End-of-life Carementioning
confidence: 99%
“…Individuals with imperious religious faith report higher levels of satisfaction, greater personal happiness, and fewer negative consequences of traumatic life events. 11 A couple of case histories reported by Sims better highlights the importance of spiritualism. In the first case, Jim who was suffering from Korsakov's psychosis was so deteriorated that he mistook his wife for a hat.…”
mentioning
confidence: 99%